Green Orientation and Digital Capabilities Driving Regional MSME Sustainability - Istiqomah, Yuliani; Pawitri, Wiwit (Inovasi Analisis Data, 2025)
Purpose: This paper investigates how organizational capabilities influence MSMEs' sustainable performance via digital financial inclusion and the contingent impact of government support. Method: Quantitative survey method was used, and partial least squares structural equation model was adopted to validate the proposed model. Findings: The results indicate that digital marketing capability, financial literacy capability, green entrepreneurial orientation and dynamic capability possess a positive impact on sustainable MSME performance. Such capabilities also multiply digital financial inclusion, which mediates in a critical way the translation of internal strengths into sustainability outcomes. Performance Based outcome It is implied that MSMEs can enhance performance when they seamlessly integrated digital financial services into their operations. Nonetheless, government support do not largely reinforce these links, indicating that institutional efforts might yet be insufficiently align with MSMEs digital and sustainability necessities at regional business level. Novelty: This study provides an integrative capability-based framework that locates digital financial inclusion as a critical means of connecting multiple organizational capabilities to sustainable MSME performance. Implications: The result of the study indicates that sustainable development of MSME is mostly to internal capability building and less by external policy support. MSME owners are advised to boost digital marketing, financial knowledge, adaptability and sustainable practices as well, to ensure they can fully capture the benefits of digital financial ecosystems. For policy-makers the results emphasize that more generic support programmes should be replaced with targeted capability building digital-embedded policies which better underpin long-term MSME sustainability.